2021
DOI: 10.1094/php-01-21-0007-rs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Application Timing of Miravis Ace for Control of Fusarium Head Blight in Wheat

Abstract: Fusarium head blight (FHB) is a serious disease of wheat and barley that not only lowers yield but also contaminates the grain with associated mycotoxins such as deoxynivalenol (DON). Chemical control options for FHB and DON include application of triazole fungicides at the anthesis or flowering stage. This presents practical challenges for growers in managing FHB, as the appropriate timing window typically lasts only 3 to 4 days. If this small window is missed, due to weather conditions or technical problems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The first experiment showed that early flowering (GS61) is the most effective timing for control of FHB and resulting DON, with an earlier application at mid-head emergence (GS55) more effective than a later application at late flowering (GS69); this in in agreement with several previous studies [16,21,23,24]. Infection by F. graminearum occurs after a rainfall event when temperatures range from 20 to 30 • C with at least 16 h of wetness [25].…”
Section: Discussionsupporting
confidence: 88%
“…The first experiment showed that early flowering (GS61) is the most effective timing for control of FHB and resulting DON, with an earlier application at mid-head emergence (GS55) more effective than a later application at late flowering (GS69); this in in agreement with several previous studies [16,21,23,24]. Infection by F. graminearum occurs after a rainfall event when temperatures range from 20 to 30 • C with at least 16 h of wetness [25].…”
Section: Discussionsupporting
confidence: 88%
“…Field surveys, as the most primitive and basic method of disease research, require relevant personnel to have lots of expertise in plant pathology and epithetics. Biochemical technology, as another mainstream technique, requires more sophisticated sampling and processing and can cause irreversible damage to experimental targets [11,12]. Both methods commonly used in the late stages of infection are practically effective [13].…”
Section: Introductionmentioning
confidence: 99%